From Psychoanalysis to Literature: Olga Tokarczuk - Pietro Pascarelli (EJP import test, 2021)
Summary: The power of the unconscious accepted as a wise window on life, and poetic intelligence; creative thought and psychoanalysis as an anthropological look at cultural worlds and our everyday life against the backdrop of the cosmos, the intimacy of the self and of an immemorial time run in all possible directions through Olga Tokarczuk’s work.
Keywords: Borders; dreams; Psychoanalysis; Tokarczuk; uncanny; Wolves